Design of reduced-order nonlinear observers for energy conversion applications - Leon, Enrique Andres (2010)
Here a systematic technique to design a reduced-order nonlinear observer for estimating signals in application to energy conversion systems is introduced. This observer presents a linear error dynamics in estimated variables and it is built in a methodical way. The proposed method has been motivated by problems arising in power conversion systems, but its use can be extended to other areas. The introduced observer is able to simplify the design of observer-based algorithms applied in power conversion systems. Examples are presented to show the advantages of the proposed method.